Development of the DAGIS intervention study: a preschool-based family-involving study promoting preschoolers' energy balance-related behaviours and self-regulation skills - Carola Ray; Riikka Kaukonen; Elviira Lehto; Henna Vepsäläinen; Nina Sajaniemi; Maijaliisa Erkkola; Eva Roos (BMC, 2019)
Abstract Background Preschoolers' energy balance-related behaviours (EBRBs) and self-regulation skills are important for their later health. Few preschool-based interventions aiming to promote preschoolers' EBRBs and self-regulation skills, simultaneously reducing differences in EBRBs, due to children's socio-economic status (SES) background, have been conducted. This study will present the Increased Health and Wellbeing in Preschools (DAGIS) intervention development process applying the Intervention Mapping (IM) framework. Methods The development of the DAGIS intervention study, a preschool level clustered randomized controlled trial (RCT), was based on the IM framework. The protocol in IM guides the development process of an intervention through six steps: needs assessment and logic model of the problem, programme outcomes and objectives, design of the programme, production, implementation plan, and evaluation plan. Results The needs assessment, part of the step 1 in IM, yielded the base for the DAGIS logic model of change. The model includes objectives related to changes in children's EBRBs, self-regulation skills, and in psychosocial and physical environment that is determined by parents and early educators. A 22-week programme was developed, and materials for preschools and families were produced. A feasibility study of the recruitment processes, acceptability of the materials and methods, and implementation was conducted. The DAGIS intervention study was conducted September 2017-May 2018 as a clustered RCT including a comprehensive effectiveness and process evaluation. The process evaluation was run throughout the intervention targeting preschools and families. Conclusion A preschool-based family-involving programme was developed in the DAGIS intervention study by applying the IM protocol. It was a time- and resource-consuming process. However, the systematic planning, development, and running of the programme have reinforced a comprehensive evaluation, which is a strength in the intervention. The results from the evaluation will enhance the knowledge of how to promote EBRBs and self-regulation skills among preschoolers, and diminish SES differences in them. Trial registration ISRCTN57165350 (Prospectively registered January the 8th, 2015).